ANALISIS FRAMING PEMBERITAAN KASUS SEPUTAR KEMACETAN LALU LINTAS DKI JAKARTA DI MEDIA ONLINE KOMPAS.COM - Giarwanto, Achmad Rizki (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2012)
Congestion in Jakarta, as has been the hallmark in the nations capital. Congestion is a situation or circumstance stagnated or even cessation of traffic caused by the large number of vehicles exceeding the capacity of the road. Congestion happens in many big cities, especially who do not have good public transportation or inadequate or unbalanced also need roads to population density, such as Jakarta. The problem of traffic jams daily in Jakarta.Cause of traffic jams occur due to several reasons: soaring private vehicle, unmet housing sector in the devel-opment of the capital, Jakartas population density, there was a flood thus slowing the vehicle, no road repairs, public transit riders and the behavior of motorists that are not orderly.The focus of discussion in this study is on the news about the case of traffic congestion in Jakarta online media Kompas.com period in March 2011. Cases around the traffic jams of Jakarta is reporting that attracted public attention, especially Jakarta residents.The research problem is to know how the media frame the news online KOMPAS.com case about a traffic jam of Jakarta in March 2011 period. The paradigm of this research using a constructivist approach. Constructivist paradigm of looking at the reality of social life is not a natural reality, but the result of the construction.This type of research is descriptive qualitative research method of framing analysis model of Robert N. Entman. With the Robert N. Entman researchers can figure out how Kompas.com online media construct reality of news surrounding the case of a traffic jam of Jakarta, which is so much a polemic that appears related to the efforts and policies of the government in breaking down the traffic congestion in Jakarta.The results of the research can be framing device models Robert N. Entman on the news about the case surround-ing the traffic congestion in Jakarta Kompas.com online media is that the frame Kompas.com further highlight the various efforts undertaken provincial government (provincial government) to address congestion Jakarta Jakarta still seems yet to bear fruit. Various provincial efforts to tackle traffic congestion in Jakarta in Jakarta, namely, restricting private vehicles, implementing ERP (the pay), limiting hours of truck operation, the construction of non-toll highways, and implement the system TOD (transit oriented development) are always taken into consider-ation for the provincial government of DKI Jakarta to parse traffic congestion in Jakarta